Green Concept: Dampak Environmental Awareness, Price Sensitivity, Trust, Value terhadap Behavioural Intentions - Alhakim, Jimmy; Hildayanti, Siti Komariah; Setiawan, Budi (Value : Jurnal Manajemen dan Akuntansi, 2025)
The trend of green concepts has gained global attention through the United Nations with 17 Sustainable Development Goals. This study analyzes the impact of green environmental awareness, green price sensitivity, green product trust, and green product value on green behaviour intentions in the green concept. It aims to provide insight to entrepreneurs and the government in developing effective green products. The Theory of Planned Behaviour (TPB) underlies this research. The research was conducted in Palembang City through an online survey for data collection, involving 96 respondents who were selected through convenience sampling. Data analysis was carried out using the Partial Least Squares Structural Equation Model (PLS-SEM) with SmartPLS 3. The results showed that green environmental awareness, green product trust, and green product value had a significant and positive effect on green behaviour intentions, while green price sensitivity had a positive but insignificant effect. This research highlights the importance of fostering environmental awareness and consumer trust in eco-friendly products and highlights the functional, emotional, and symbolic value of green products in encouraging green behaviour.